Frequency of Antigen Dia in academics of a university in the state of Santa Catarina, Brazil (Brazilian Journal of Health Research, 2023)
Introduction:The Diª Antigen is part of the Diego blood group system. It has a low frequency in the general population (1 to 6%), but with higher frequency in Asian (10%) and indigenous (36%) populations. The Brazilian ethnic composition is influenced by the indigenous ethnicity. Objectives: Identify carriers and establish the phenotypic frequency of the Diª antigen in university students from a university in Santa Catarina state - Brazil. Detect carriers of rare DI phenotype (a+ b-). Contribute with information to the hemodiagnostic reagents industry about manufacture of reagents for the identification of these irregular antibodies. Methods: Sixty-five blood samples were collected and submitted to the erythrocyte phenotyping method to identify the Diª antigen through tube hemagglutination tests with anti-Diª serum. Data on birthplace, ethnic descent and information about blood transfusion, blood donation and diseases history were collected from those enrolled for research. Results: Diª antigen phenotype was positive in 1.5% of the sample. The positive sample was an individual of indigenous descent, born in a region whose indigenous population was part of the ethnic composition. Of the sample studied, 25.8% declared themselves to be of indigenous descent. Conclusion: Although infrequent, it is possible to identify the Diª antigen in the population studied, since the indigenous ethnicity is part of the ethnic composition.
Keywords: Blood groups; Antigens; Phenotype